High Thyroid Stimulating Hormone Level Is Associated With Hyperandrogenism in Euthyroid Polycystic Ovary Syndrome (PCOS) Women, Independent of Age, BMI, and Thyroid Autoimmunity: A Cross-Sectional Analysis - Cai, Jie; Zhang, Yi; Wang, Yuying; Li, Shengxian; Wang, Lihua; Zheng, Jun; Jiang, Yihong; Dong, Ying; Zhou, Huan; Hu, Yaomin; Ma, Jing; Liu, Wei; et al. (Frontiers in Endocrinology, 2019)
1) Background: Infertility and dyslipidemia are frequently present in both women with polycystic ovary syndrome (PCOS) and subjects with thyroid dysfunction. Limited study regarding the association between thyroid stimulating hormone (TSH) level and phenotypes in euthyroid PCOS women. We aimed to determine whether the variation of TSH level associates with phenotypes in euthyroid PCOS patients. 2) Methods: Cross-sectional study including 600 PCOS and 200 age, body mass index (BMI) and thyroid autoimmunity-matched Chinese women from Renji hospital, Shanghai Jiaotong university during January 2010 and August 2018. The anthropometric and serum biochemical parameters related to TSH, thyroid autoimmunity, lipid profiles and sex steroids were detected. 3) Results: The TSH level is higher in (2.29±1.24 vs 1.86±0.90 mU/L, p<0.001) in PCOS than controls. In euthyroid PCOS patients, TSH, TG, TC, LDL-c and apoB level increased from non-hyperandrogenism (nonHA) to HA group (all p<0.05). TSH level is positively associated with TG, apoB, free T, FAI and negatively associated with apoA (all p<0.05). The percentage of HA increased from TSH level (57.93% in TSH≦2.5 group vs. 69.46% in TSH>2.5mU/L group, p=0.006). HA phenotype is increased with TSH level independently of age, BMI, WC, LDL-C. Besides, in multivariate logistic regression analysis TSH and TG significantly associated with HA phenotype. 4) Conclusions: Higher TSH level is associated with increased prevalence of HA phenotype independent of age, BMI and thyroid autoimmunity in euthyroid PCOS.